MEDYCYNA W DRUKACH BAZYLIAŃSKICH XVIII W. - Getka, Joanna (Acta Neophilologica, 2018)
Advice on the treatment of humans and animals published in Basilans’ handbooks and calendars are an excellent material for studying the history of the development of medicine and veterinary medicine in the territories of the Republic of Poland in the eighteenth century. They provide information about the state of medicine, known diseases and their treatment.